2005
DOI: 10.1128/iai.73.7.4138-4145.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Pst System Reduces the Virulence of an Avian Pathogenic Escherichia coli O78 Strain

Abstract: Escherichia coli O78 strains are frequently associated with extraintestinal diseases, such as airsacculitis and septicemia, in poultry, livestock, and humans. To understand the influence of the pst operon in the virulence of E. coli, we introduced mutations into the pst genes of the avian pathogenic E. coli (APEC) O78:K80 strain 7122 by allelic exchange. The mutation of pst genes led to the constitutive expression of the Pho regulon. Furthermore, the virulence of APEC strain 7122 in a chicken infection model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(125 citation statements)
references
References 66 publications
2
118
1
4
Order By: Relevance
“…Inactivation of the pts system has been reported to render an exPEC strain avirulent (Daigle et al, 1995). In APEC, PhoB was identified to be a putative virulence factor by SCOTS (Dozois et al, 2003), and subsequent in vivo experiments with an isogenic pts mutant confirmed the findings (Lamarche et al, 2005). Other regulatory networks in APEC remain to be identified.…”
Section: Progress Towards Unravelling Apec Virulence Factorssupporting
confidence: 58%
See 1 more Smart Citation
“…Inactivation of the pts system has been reported to render an exPEC strain avirulent (Daigle et al, 1995). In APEC, PhoB was identified to be a putative virulence factor by SCOTS (Dozois et al, 2003), and subsequent in vivo experiments with an isogenic pts mutant confirmed the findings (Lamarche et al, 2005). Other regulatory networks in APEC remain to be identified.…”
Section: Progress Towards Unravelling Apec Virulence Factorssupporting
confidence: 58%
“…One such well-recognized system is the BarAUvrY two-component system, which has been shown to regulate APEC virulence by down-regulating type 1 and Pap fimbriae, by increasing susceptibility to oxidative stress and by reducing the amount of surface polysaccharide (Herren et al, 2006). In addition, a specific phosphate transport system (Pts) has also been linked with virulence in APEC x7122 strain (Lamarche et al, 2005). The Pts system mediates uptake of phosphate by serving as a primary sensor for extracellular phosphate levels, and its inactivation results in constitutive expression of the Pho regulon.…”
Section: Progress Towards Unravelling Apec Virulence Factorsmentioning
confidence: 99%
“…57,58 E. coli posses two Pi transport systems, a high-affinity phosphate transport and low affinity Pi transporter called Pst and Pit system, respectively. 59 Inactivation of the Pst system attenuate virulence of both extraintestinal pathogenic E. coli (ExPEC) and enteropathogenic E. coli (EPEC) strains [60][61][62][63][64] (7,15,19,24,42). In pst operon UPEC mutants, Pho regulon is activated even under phosphate-replete conditions, reducing colonization of the murine urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…P. mirabilis HI4320 possesses a pst operon identical in gene organization to that observed in Escherichia coli. Previous studies have suggested that the roles of the Pst transport system in pathogenesis include regulation of invasion (Lucas et al, 2000;Mathew et al, 2001;Sinai & Bavoil, 1993), antibiotic resistance (Soualhine et al, 2005), colonization (Buckles et al, 2006;Daigle et al, 1995;Lamarche et al, 2005;Orihuela et al, 2001;Peirs et al, 2005;Runyen-Janecky et al, 2005), and biofilm formation (Monds et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…P. mirabilis HI4320 possesses a pst operon identical in gene organization to that observed in Escherichia coli. Previous studies have suggested that the roles of the Pst transport system in pathogenesis include regulation of invasion (Lucas et al, 2000;Mathew et al, 2001;Sinai & Bavoil, 1993), antibiotic resistance (Soualhine et al, 2005), colonization (Buckles et al, 2006;Daigle et al, 1995;Lamarche et al, 2005;Orihuela et al, 2001;Peirs et al, 2005;Runyen-Janecky et al, 2005), and biofilm formation (Monds et al, 2001).Since (i) earlier work has alluded to the importance of this system during biofilm formation (Monds et al, 2001(Monds et al, , 2007 and (ii) the formation of crystalline biofilms is a characteristic of UTIs associated with P. mirabilis, we hypothesized that the Pst system of P. mirabilis HI4320 is involved in biofilm formation during establishment of a UTI. To assess the role of the Pst system, this study focused upon determining previously undetected in vitro phenotypes of the Dpst mutants by comparing biofilm formation between the wild-type HI4320 and DpstA and DpstS mutants via confocal laser scanning microscopy (CLSM) and quantitative analysis of surface coverage, and by comparing in vitro protein expression of these strains grown planktonically and as a biofilm.…”
mentioning
confidence: 99%